Psychometric properties of the ASEBA older adult self report in a Mexican sample - Portillo Reyes, Veronica (2022)
Globally, large increases in older adult populations require that psychological assessments are tailored to evaluate psychopathology by considering both language and culture. In Mexico, there are little to no assessment tools which measure multiple areas of psychopathology specific to older adults. The current study tested the psychometric properties of the Spanish version of Older Adult Self Report (OASR) from Achenbach System of Empirically Based Assessment (ASEBA). The OASR was completed by 308 older adults in Mexico. Confirmatory factor analyses tested the fit of the 7-syndrome OASR model originally derived from a U.S. sample. The primary model fit index (Root Mean Square Error of Approximation) showed good fit for individuals from Mexico, while the secondary model fit indices (Comparative Fit Index/Tucker-Lewis Index) showed acceptable to good fit. The items loaded strongly on their respective syndrome factors, with a median loading of .57. By syndrome, the overall median loadings ranged from .414 (Worries) to .643 (Memory/Cognition Problems); and 98.23% of the loadings were statistically significant. The Latin American Spanish OASR demonstrated proper psychometric properties for the sample indicating that it is suitable for use with older adults in or from Mexico. The OASR offers 7 empirically based clinical constructs that are appropriate for older adults in or from Mexico. It provides a structure which can use to assess and communication issues of psychopathology and adaptive functioning improving overall care and research in geriatric psychiatry, notably when considering diverse populations.